Research on the contact fatigue failure of thermal sprayed coating based on infrared thermography. Issue 1 (2nd January 2020) - Ma, Runbo; Dong, Lihong; Wang, Haidou; Guo, Wei
ABSTRACT: Aiming to improve the accuracy of the contact life prediction of sprayed coatings, a series of contact fatigue tests are conducted on RM-1 tester. Five kinds of plasma sprayed Al2 O3 –40 wt%TiO2 composite ceramic coatings (AT40 ceramic coatings) of different quality and surface performance parameters are tested on the principle of central composite design. The passive infrared thermography is used to monitor the temperature change of the coating during the process of contact fatigue failure. The findings reveal that the infrared signal which is characteristic of non-stationary stochastic process shows a pre-warning against the failure of coatings. Both singularity detection and k-means clustering analysis come to a conclusion that the invalidating process of coating caused by contact fatigue is an interwoven result of crack initiation, crack propagation and crack instability fracture, etc. The nonstationarity of the infrared signal is further verified by non-parametric hypothesis test. Based on the results of correlation analysis between the contact point temperature range of the coating surface and the contact fatigue life, a reliable nonlinear prediction model is established.